Bis(dicyclohexylammonium 4-hydroxy-benzoate) - Zain, Sharifuddin Md; Ng, S.W. (International Union of Crystallography, 2007)
In the crystal structure of the title compound, 2C(12)H(24)N(+)center dot 2C(7)H(5)O(3)(-), the cation is linked to the single-bonded carboxylate O atom of an anion as well as to the double-bonded carbonyl O atom of another anion to form a centrosymmetric hydrogen-bonded ion pair. Adjacent ion pairs are linked through the hydroxy group of the anion to produce a honeycomb-like layer structure.